Recovery of International Maintenances. Strengthening Children's Rights in Nicaragua - Rivera Zamora, Xiomara (2024)
This paper comprises, in general terms, the content of the Convention on the international recovery of child support and other forms of family maintenance of 2007. It approaches the topic from a doctrinal perspective, international regulations and Nicaraguan domestic law, and emphasizes the purposes pursued by the Convention on this sensitive human right; the petitions available to creditors and debtors; and, the role of the Central Authorities in charge of the Convention’s enforcement, their functions and procedures to follow, in order to enable the feeding right of children, adolescents, and other family members. This work makes it possible to visualize the opportunity that the aforementioned legal instrument between contracting States offers, that the State of Nicaragua is part of, for the realization of the right to food for family members, which makes it necessary to properly know and manage it.